AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Rahadi, Farhan Dama; Lautania, Maya Febrianty; Nadirsyah, Nadirsyah; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study aims to examine the influence of human resource development, regulatory compliance, and monitoring intensity on the performance accountability of government agencies. The population consists of 20 Regional Government Work Units (SKPD) in Aceh Jaya Regency. The sample includes heads of departments, secretaries, heads of general and staffing sub-divisions, and heads of planning and finance sub-divisions, selected through purposive sampling, with a total of 80 respondents. This study uses primary data collected through surveys using questionnaires measured on a Likert scale of 1 to 5. The data were analyzed using multiple linear regression with SPSS 26 software. The findings indicate that human resource development, regulatory compliance, and monitoring intensity have a significant and positive effect on the performance accountability of government agencies. Additionally, the independent variables in this study explain 65,3% of the variance in government agency performance accountability. These results suggest that strengthening human resource development, regulatory compliance, and monitoring intensity can enhance government accountability.